Incarcerated spiegel hernia: laparoscopic intraperitoneal onlay mesh plus repair: a case report - Lopes, André; Mesquita, Hugo; Pinto, José P.; Santos, Andreia; Fernandes, Ricardo; Santos, Anita; Peixoto, Inês; Araújo, Rita; Alpoim, Carlos (International Surgery Journal, 2024)
Spiegel hernia (SH) is a rare lateral ventral hernia. Due to its anatomic location, diagnosis can be challenging and often delayed. Incarceration rates are significantly high, increasing the risk of strangulation. Therefore, surgery is the primary treatment. We present the case of a 78-year-old female patient admitted to the emergency room for intestinal obstruction due to an incarcerated SH. The patient underwent exploratory laparoscopy with intraperitoneal onlay mesh (IPOM) plus repair.